Work-Family Balance and Psychosocial Adjustment of Married International Students - Bulgan, Gökçe; Çiftçi, Ayşe (Journal of International Students, 2018)
The authors investigated how work-family balance mediated the relationship between personality traits, gender roles, social support, and psychosocial adjustment. Data were collected from 243 married international graduate students (MIGSs) studying in the United States. Results of structural equation modeling indicated that personality traits influence the psychosocial adjustment process. In addition, being extraverted, agreeable, and conscientious contributed to balancing academic and family life, whereas having neurotic tendencies such as experiencing depression and anxiety diminished work-family balance. Work-family balance did not mediate the relationship between personality traits, gender roles, social support, and psychosocial adjustment. The authors discussed the findings by considering clinical implications and making suggestions for future research.